Cronobacter sakazakii infection alters serotonin transporter and improved fear memory retention in the rats - Sivamaruthi, Bhagavathi Sundaram; Madhumita, Rajkumar; Balamurugan, Krishnaswamy; Emmanuvel Rajan, Koilmani (Frontiers in Pharmacology, 2015)
It is well established that Cronobacter sakazakii infection cause septicemia, necrotizingenterocolitis (NEC) and meningitis. In the present study, we tested whether the C. sakazakii infection alter the learning and memory through serotonin transporter (SERT). To investigate the possible effect on SERT, on postnatal day (PND)-15, wistar rat pups were administered with single dose of C. sakazakii culture (Infected group: IF; 107 CFU) or 100μL of Luria-Bertani broth (LB; Medium Control: MC) or without any treatment (Naïve control: NC). All the individuals were subjected to passive avoidance test on PND-30 to test their fear memory. We show that single dose of C. sakazakii infection improved fear memory retention. Subsequently, we show that C. sakazakii infection induced the activation of Toll-like receptor-3 (TLR-3) and heat-shock proteins-90 (Hsp-90). On the other hand, level of serotonin (5-HT) and SERT protein was down-regulated. Furthermore, we show that C. sakazakii infection up-regulate microRNA (miR)-16 expression. The observed results highlight that C. sakazakii infections was responsible for improved fear memory retention and may have reduced the level of SERT protein, which is possibly associated with the interaction of up-regulated Hsp-90 with SERT protein or miR-16 with SERT mRNA. Taken together, observed results suggest that C. sakazakkii infection alter the fear memory possibly through SERT. Hence, this model may be effective to test the C. sakazakii infection induced changes in synaptic plasticity through SERT and effect of other pharmacological agents against pathogen induced memory disorder.